(untitled) (Journal of Asian Development Studies, 2018)
Globalization can contribute very much to reduce poverty both directly and by accelerating growth. However, its impact to reduce poverty in developing countries is very limited because of domestic policy failures. For an economist study of relationship between globalization and rural poverty is very important that how much the role of globalization on rural poverty is supporting for its reduction. To know about its impact a study was conducted on the basis of time series secondary data. After the research it is found that impact of globalization on rural poverty was insignificant whereas there was positive relationship between agricultural product, literacy rate and globalization. Along with these, agricultural product and literacy rate were highly correlated but there exists very weak relationship between globalization and rural poverty. It is also found that impact of agriculture products and literacy rate to reduce rural poverty was significant. In the end it is concluded that impact of globalization to reduce rural poverty is still insignificant but its impact to improve agricultural products and literacy rate is very much striking. So during the formulation and execution of different policies it is necessary for authorities to capture the most of benefits of trade with this global world to wipe out poverty from the country